Legal Liability for Force Majeure in Digital Crypto Asset Contracts Reviewed from the Perspective of Legal Rationality in the Digital Age: Tanggung Jawab Hukum atas Keadaan Force Majeure dalam Kontrak Digital Aset Kripto Ditinjau dari Rasionalitas Hukum di Era Digital - Amara Diva Abigail; Diah Ayuning Tyas; Fendi Setyawan; M. Arief Amrullah (Academia Open, 2025)
General Background: The rapid advancement of digital technology has transformed legal relations through the emergence of smart contracts and crypto asset transactions operating autonomously on blockchain systems. Specific Background: Although these digital contracts promise efficiency and certainty, their automated and decentralized nature raises complex legal issues when force majeure events—such as cyberattacks, system failures, or sudden regulatory changes—disrupt contractual performance. Knowledge Gap: Existing civil law doctrines on force majeure and contractual liability are primarily designed for human-centered agreements and remain inadequate to address responsibility in algorithm-driven systems, particularly within Indonesia’s legal framework. Aims: This study aims to analyze legal liability for force majeure in crypto asset digital contracts through a philosophical examination of legal rationality in the digital era. Results: Using normative–philosophical analysis, the study finds that traditional fault-based liability and positivistic legal rationality require reconstruction to accommodate technological risks and automated execution. Novelty: The research introduces an adaptive, reflective conception of legal rationality that integrates technological realities with principles of justice, certainty, and utility. Implications: These findings imply the need for explicit force majeure clauses, shared responsibility models, and adaptive legal interpretation to ensure fair and effective regulation of digital contracts in the evolving crypto ecosystem. Highlights: Force majeure in crypto-based smart contracts involves technological and regulatory risks beyond traditional doctrines. Automated and decentralized contract execution challenges fault-based and human-centered legal liability concepts. Adaptive legal rationality is essential to balance legal certainty, justice, and technological innovation in the digital era. Keywords: Force Majeure, Digital Contracts, Crypto Assets, Legal Liability, Legal Rationality